(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Human dignity has gradually emerged as a central value within contemporary constitutional systems and the broader framework of international human rights protection. It is founded upon the recognition that every person possesses intrinsic value, forming the normative basis of freedom, equality, justice, and democratic order. While the Indian Constitution does not contain a distinct provision specifically guaranteeing dignity, constitutional jurisprudence has steadily interpreted Article 21 to include the entitlement to a dignified existence. Through judicial innovation, the concept of life has expanded beyond mere animal existence to include privacy, livelihood, shelter, healthcare, autonomy, reputation, and protection from degrading treatment. This study undertakes a critical examination of the evolution of dignity-based constitutional jurisprudence in India, focusing primarily on the interpretation of Article 21. The analysis also places Indian constitutional developments within a comparative framework by examining major international human rights instruments and selected constitutional experiences from Germany, South Africa, and European jurisdictions. The study argues that dignity has become a transformative legal principle capable of humanizing state power and strengthening constitutional democracy. However, practical barriers such as poverty, discrimination, custodial abuse, gender violence, and technological surveillance continue to threaten its realization. The paper concludes that dignity must move beyond symbolic recognition and become an enforceable social reality through coordinated action by courts, legislatures, governments, and civil society.